Role of Urban Agriculture in Promoting Food Security and Sustainable Cities - Ghimire, Bidhya Jyoti (Journal of Research and Development, 2024)
Urban agriculture is often not widely discussed in the development process, but the increasing migration of people from rural areas to urban centers has raised awareness of its importance, particularly in relation to sustainable food security in city areas. This study explores the multifaceted role of urban agriculture in addressing contemporary urban challenges, with a focus on food security and sustainability. The objectives of the paper are to comprehensively analyze the benefits and challenges associated with urban agriculture, identify key themes and trends through a review of existing literature, and examine global case studies to provide practical perception in implementation and impact of urban agriculture initiatives. Employing qualitative, inclusive review of literature and case studies, the paper summarizes major arguments related to the transformative potential of urban agriculture in fostering sustainable urban development. Findings highlight the importance of community engagement, policy integration, and technological innovation in enhancing the resilience and effectiveness of urban agriculture initiatives. Urban agriculture supports food security by providing reliable access to fresh affordable food with city limits and also contributes in creating eco-friendly cities by incorporating green spaces, reducing waste through composting and utilizing sustainable practices like rooftop gardens and vertical farms.